2021
DOI: 10.1002/cam4.3766
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition intervention is beneficial to the quality of life of patients with gastrointestinal cancer undergoing chemotherapy in Vietnam

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 55 publications
2
14
0
2
Order By: Relevance
“…In the present study, we showed that intensive nutrition counselling commencing at diagnosis and continuing for 18 weeks had no marked impact on QoL over 12 months. Only a few published studies are available to understand the impact of nutrition counselling interventions on changes in QoL in people undergoing treatment for cancer, and the results are conflicting [ 15 , 34 , 35 , 36 ]. An RCT tested a three-month nutrition intervention plus three-month follow-up in cancer outpatients and found no significant difference in QoL or nutritional status between intervention ( n = 30) and control groups ( n = 28), despite achieving a higher protein and energy intake [ 36 ]; this study also had a high withdrawal rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we showed that intensive nutrition counselling commencing at diagnosis and continuing for 18 weeks had no marked impact on QoL over 12 months. Only a few published studies are available to understand the impact of nutrition counselling interventions on changes in QoL in people undergoing treatment for cancer, and the results are conflicting [ 15 , 34 , 35 , 36 ]. An RCT tested a three-month nutrition intervention plus three-month follow-up in cancer outpatients and found no significant difference in QoL or nutritional status between intervention ( n = 30) and control groups ( n = 28), despite achieving a higher protein and energy intake [ 36 ]; this study also had a high withdrawal rate.…”
Section: Discussionmentioning
confidence: 99%
“…An RCT tested a three-month nutrition intervention plus three-month follow-up in cancer outpatients and found no significant difference in QoL or nutritional status between intervention ( n = 30) and control groups ( n = 28), despite achieving a higher protein and energy intake [ 36 ]; this study also had a high withdrawal rate. In contrast, a quasi-experimental trial of a two-month nutrition intervention for people with gastric or colon cancer ( n = 53), commencing during an inpatient stay, found improved global QoL (EORTC QLQ-C30) and improvements in scores of physical functioning and role functioning compared with the control group ( n = 50) [ 35 ]. Similarly, a 12-week RCT in people with gastrointestinal or head and neck cancer receiving radiotherapy found that intensive nutrition counselling ( n = 29) mitigated weight loss and improved global QoL scores and physical function scale scores (EORTC QLQ-C30) compared with the control group ( n = 31) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…While these patients are prone to malnutrition and weight loss during their treatment, many are overweight due to obesity being a major risk factor for cancers of the colon, rectum, esophagus, liver, and pancreas [ 71 ]. Nguyen et al examined how nutritional interventions improved the QoL in patients with GI cancer who were undergoing CT in Vietnam [ 36 ] ( Table 1 ). Patients with early-stage GI cancers tend to be asymptomatic and thus this disease tends to be detected later with a poorer prognosis [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, QoL is an important endpoint that is used to assess the treatment outcomes among those with GI cancers [ 65 ]. When GI patients received high-protein and energy-rich diets, they had higher QoL scores when they were compared to those of the control as well as reduced adverse effects from their CT regimen [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…They could freely select their own diet. In contrast, patients in the intervention group were treated with the intervention regimen, which consisted of: (1) nutritional counseling; (2) hospital meals: each patient was assigned a specific menu prepared by research members during the time of staying at the hospital; (3) instruction on food preparation at home: before discharge, patients were instructed on preparing their diet at home with high energy and protein intake as recommended and given formula milk (6 teaspoons, equivalent to 54 g of powdered milk with 180 mL warm water per time) within two months [ 20 ]. To monitor the intervention process, the dieticians continuously evaluated the daily diet of each patient during hospitalization and tele-counseling every two weeks for weight monitoring and nutritional support advice after discharge.…”
Section: Methodsmentioning
confidence: 99%